An introduction to Africana philosophy - Gordon, Lewis R. (Lewis Ricardo), 1962- (Cambridge, UK ; New York : Cambridge University Press, 2008)
"In this book Lewis R. Gordon offers the first comprehensive treatment of Africana philosophy, beginning with the emergence of an Africana (i.e., African diasporic) consciousness in the Afro-Arabic world of the Middle Ages. He argues that much of modern thought emerged out of early conflicts between Islam and Christianity that culminated in the expulsion of the Moors from the Iberian Peninsula, and from the subsequent expansion of racism, enslavement, and colonialism which in their turn stimulated reflections on reason, liberation, and the meaning of being human. His book takes the reader on a journey from Africa through Europe, North and South America, the Caribbean, and back to Africa, as he explores the challenges posed to our understanding of knowledge and freedom today, and the response to them which can be found within Africana philosophy."--Jacket
Introduction: Africana philosophy in context -- Part I: Groundings -- Africana philosophy as a modern philosophy -- Classic eighteenth- and nineteenth-century foundations -- Anton Wihelm Amo -- Quobna Ottobah Cugoano -- From David Walker's Appeal to the founding of the American Negro Academy -- Two Caribbean men of letters : Anténor Firmin and George Wilmot Blyden -- Conclusion -- Part II: From New World to new worlds -- Three pillars of African-American philosophy -- Anna Julia Cooper and the problem of value -- W.E.B. Du Bois and the problem of double consciousness -- Fanon's critique of failed dialectics of recognition -- Africana philosophical movements in the United States and Britain -- Prophetic and other recent forms of African-American pragmatism -- Black feminist and womanist thought -- Afrocentrism and Afrocentricity -- African-American analytical philosophy -- African-American and Afro-British European continental philosophy -- Cedric Robinson's anthropology of Marxism -- African-American existential philosophy, phenomenology, and their influence -- Afro-Caribbean philosophy -- African philosophy -- African humanism -- The theme of invention in recent African philosophy -- African critiques of invention -- Recent African political thought -- Conclusion
Includes bibliographical references and index
Keywords: Philosophy, African